Organ and tissue donation - Healey, Justin (Issues in society (Balmain, N.S.W.), 2011)
Organ and tissue transplants can be the last resort for a range of life-saving and life-improving treatments. Although the latest organ donation figures have reached a record high, the total however, only equates to a national organ donor rate of 13.8 per million, which suggests more can be done to help Australians who are on transplant waiting lists. This book addresses the misconceptions and facts about organ and tissue donation and registration with the aim of raising community awareness in an effort to boost donation rates. It also explores a range of ethical issues around consent and obje.